Fibromyalgia syndrome: still a medical dilemma - F. Atzeni; P. Sarzi-Puttini; S. Perrot (PAGEPress Publications, 2012)
This issue of "Reumatismo" deals with a variety of aspects of chronic widespread pain (CWP) and its rheumatological quasi-synonym of fibromyalgia (FM). The definitions of CWP and FM both have a long history. Chronic musculoskeletal pain conditions are universally prevalent in both genders and all age groups and, although their pathophysiology varies, they are inter-related anatomically and by their association with pain and impaired physical function. However, there is still no consensus as to whether FM should be considered a discrete entity or just the tip of the iceberg of CWP...